Optimalisasi Maṣlaḥah ‘Āmmah Dalam Konstruksi Maritim: Perspektif Manajemen Produksi Islam Pada Bell Rock Lighthouse - Komaria, Siti; Hasanah, Ummiyatul; Ramdlaniyatul Q, Siti; Sam’a, Ulfatus; Ratnayawati, Dina; Kunaifi, Aang (Ekosiana Jurnal Ekonomi Syari ah, 2025)
This study aims to analyze the construction of the Bell Rock Lighthouse from the perspective of Islamic production management, focusing on the application of the principle of maṣlaḥah ʿāmmah (public interest) and Sharia values such as ihsan, ḥifẓ al-nafs (protection of life), and equitable and accountable capital management. The research adopts a literature review method, examining secondary sources in the form of documentary videos, news reports, and relevant historical articles. Data were analyzed descriptively and comparatively to identify the alignment between the project’s production management practices and the principles of Islamic production management. The analysis reveals that the construction process of the Bell Rock Lighthouse reflects principles of perseverance, professionalism, and integrity, demonstrated through meticulous planning, effective workforce management, the use of innovative construction technology, and a focus on long-term benefits for maritime safety. The principle al-maṣlaḥah al-ʿāmmah muqaddamah ʿala al-mafsadah was practically implemented, prioritizing public safety without causing economic or social harm. This study affirms that the application of Islamic production management in infrastructure projects not only enhances output quality but also strengthens the ethical dimension and ensures broader societal benefits. The findings are relevant for developing policies and practices in Islamic production management within the modern context, particularly for large-scale public projects. Keyword: Islamic production management, maṣlaḥah ʿāmmah, ḥifẓ al-nafs, Bell Rock Lighthouse, maritime construction